A Second, Druggable Binding Site in UDP‐Galactopyranose Mutase from Mycobacterium tuberculosis?. (7th November 2016) - Shi, Yun; Colombo, Cinzia; Kuttiyatveetil, Jijin R. A.; Zalatar, Nataliya; van Straaten, Karin E.; Mohan, Sankar; Sanders, David A. R.; Pinto, B. Mario
Abstract: UDP‐galactopyranose mutase (UGM), a key enzyme in the biosynthesis of mycobacterial cell walls, is a potential target for the treatment of tuberculosis. In this work, we investigate binding models of a non‐substrate‐like inhibitor, MS‐208, with M. tuberculosis UGM. Initial saturation transfer difference (STD) NMR experiments indicated a lack of direct competition between MS‐208 and the enzyme substrate, and subsequent kinetic assays showed mixed inhibition. We thus hypothesized that MS‐208 binds at an allosteric binding site (A‐site) instead of the enzyme active site (S‐site). A candidate A‐site was identified in a subsequent computational study, and the overall hypothesis was supported by ensuing mutagenesis studies of the A‐site. Further molecular dynamics studies led us to propose that MS‐208 inhibition occurs by preventing complete closure of an active site mobile loop that is necessary for productive substrate binding. The results suggest the presence of an A‐site with potential druggability, opening up new opportunities for the development of novel drug candidates against tuberculosis. Abstract : Second site : NMR and MD experiments have unveiled a possible second binding site on UDP‐galactopyranose mutase (UGM), a target for tuberculosis. The best MD model showed that the investigated inhibitor bound at an allosteric site rather than the substrate‐binding site. This was corroborated by experimental results from NMR spectroscopy, kinetic assays, and mutagenesis.